Evidence That the Hormonal Contraceptive Pill Is Associated With Cosmetic Habits - Batres, Carlota; Porcheron, Aurélie; Kaminski, Gwenaël; Courrèges, Sandra; Morizot, Frédérique; Russell, Richard (Frontiers in Psychology, 2018)
Hormonal contraception is known to cause subtle but widespread behavioral changes. Here, we investigated whether changes in cosmetic habits are associated with use of the hormonal contraceptive pill. We photographed a sample of women (N=36) who self-reported whether or not they use the contraceptive pill, as well as their cosmetic habits. A separate sample of participants (N=143) rated how much makeup these target women appeared to be wearing. We found that women not using the contraceptive pill (i.e., naturally-cycling women) reported spending more time applying cosmetics for an outing than did women who use the contraceptive pill. We also found that the faces of these naturally-cycling women were rated as wearing more cosmetics than the faces of the women using the contraceptive pill. Thus, we found clear associations between contraceptive pill use and makeup use. This provides evidence consistent with the possibility that cosmetic habits, and grooming behaviors more generally, are affected by hormonal contraception.